Assessment of Heavy Metals pollution in the soil of Oilfield West Qurna-1 in Basra City, Iraq - Ghanem, Abdullah M.; Issa , Murtadha Jabbar (Iraqi Journal of Science, 2026)
This study aims to assess the degree of contamination by heavy metals in the topsoil of the oilfield West Qurna-1. After collecting 16 soil samples in October 2023, the results were classified as sandy sludge. The research region has a soil organic matter (OM) concentration of 3.6%, a pH level of 7.8, and a soil salinity of 8%. Soil samples collected from the oilfield WQ-1 contained detectable levels of heavy metals compared with national and world limits They had moderate levels for. Cr=255.6 ppm, Ba=445.3 ppm, Rb=46.3 ppm, and high levels of heavy metals Ni=170.6 ppm, Sr=716.5 ppm, Cu=64.6 ppm, Br=128.8 ppm, and Zn=122.4 ppm. The basis for evaluating heavy metal contamination was using the Contamination Factor (CF), Geoaccumulation Index (I-geo), Pollution Load Index (PLI), and Enrichment Factor (EF), all of which indicated that the samples had a high level of contamination. Bromine was the most severely contaminated element, and copper, strontium, and chromium were moderately contaminated.